2023
DOI: 10.1021/acs.jpclett.3c00358
|View full text |Cite
|
Sign up to set email alerts
|

Guanine Quantum Defects in Carbon Nanotubes for Biosensing

Abstract: Fluorescent single-wall carbon nanotubes (SWCNTs) are used as nanoscale biosensors in diverse applications. Selectivity is built in by noncovalent functionalization with polymers such as DNA. Recently, covalent functionalization was demonstrated by conjugating guanine bases of adsorbed DNA to the SWCNT surface as guanine quantum defects (g-defects). Here, we create g-defects in (GT)10-coated SWCNTs (Gd-SWCNTs) and explore how this affects molecular sensing. We vary the defect densities, which shifts the E 11 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
(127 reference statements)
0
7
0
Order By: Relevance
“…Additionally, Weisman et al developed a protocol to covalently attach guanine bases to the lattice of SWCNTs. These defects cause quantum light emission from the coupled defect states. This approach can also be used directly for biosensing or conjugation of larger recognition motifs to create sensors for bacterial or viral motifs. , Diazonium chemistry also offers to conjugate more complex entities such as biomolecules. , It is useful to directly attach, for example, nanobodies or grow peptide chains on the SWCNT lattice, which expands the toolbox for many applications such as sensing with quantum defects. , The concentration of diazonium salt affects the reaction and, most likely, the density of quantum defects. The fluorescence intensity ratio I E 11 * / I E 11 between the quantum-defect-related emission (E 11 *) and the bandgap emission (E 11 ) of SWCNTs is regarded as an approximate measure for defect density .…”
mentioning
confidence: 99%
“…Additionally, Weisman et al developed a protocol to covalently attach guanine bases to the lattice of SWCNTs. These defects cause quantum light emission from the coupled defect states. This approach can also be used directly for biosensing or conjugation of larger recognition motifs to create sensors for bacterial or viral motifs. , Diazonium chemistry also offers to conjugate more complex entities such as biomolecules. , It is useful to directly attach, for example, nanobodies or grow peptide chains on the SWCNT lattice, which expands the toolbox for many applications such as sensing with quantum defects. , The concentration of diazonium salt affects the reaction and, most likely, the density of quantum defects. The fluorescence intensity ratio I E 11 * / I E 11 between the quantum-defect-related emission (E 11 *) and the bandgap emission (E 11 ) of SWCNTs is regarded as an approximate measure for defect density .…”
mentioning
confidence: 99%
“…126−129 Galonska and Kruss et al demonstrated enhanced sensitivity in detecting dopamine by using (GT) 10 -ssDNA-coated (6,5)-SWCNTs, specifically through covalent bonding that introduced guanine quantum defects. 130 Covalent sp 3 defects on carbon nanotubes (also called organic color centers) (6,5)-(GT) 15 were used in monitoring autophagy-associated lysosomal acidification in vivo and were designed to detect pH changes in the lysosomal environment of living cells and in vivo models. 131 The utilization of time-correlated single-photon counting techniques has provided insights into the photoluminescence lifetime of the E 11 * defect emission, demonstrating a notable extension compared to the lifetime of mobile excitons.…”
Section: Chirality-sorted/monochiral Swcntsmentioning
confidence: 99%
“…As 1 O 2 reacts 2 orders of magnitude faster with guanine compared to other nucleobases, predominantly guanine endoperoxides are formed. These intermediates react in a cycloaddition between the guanine carbon 8 and the nearby SWCNT surface and lead to covalent attachments of guanine bases to SWCNTs . As defect density depends on the RB concentration and the guanine content, one can pattern and tailor SWCNT surfaces. , Apart from the mechanistic and photophysical studies concerning this reaction, ,, as well as the signal observed upon the adsorption of small molecules, this chemistry has up to our knowledge not been used for rational sensing.…”
Section: Introductionmentioning
confidence: 99%